2009
DOI: 10.1002/ajpa.21131
|View full text |Cite
|
Sign up to set email alerts
|

Stature estimation formulae for indigenous North American populations

Abstract: Stature estimation methods for adult indigenous humans from the Americas have generally relied on a limited number of regression equations. The available equations, however, are not broadly applicable to the diversity of the populations that lived in the New World prior to European colonization. Furthermore, some equations that have been used were originally derived from inappropriate reference samples, such as the "Mongoloid" group measured by Trotter and Gleser (Am J Phys Anthropol 16 [1958] 79-123). This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 45 publications
(67 reference statements)
4
111
2
5
Order By: Relevance
“…These comparisons showed that, when males and females are considered together, individuals from Fuego-Patagonia had a crural index that was most similar to that of the Temperate North American groups (Auerbach and Ruff 2010). Thus, the stature estimation formulae for Temperate groups (Auerbach and Ruff 2010) were applied in this study. Additionally, the formulae developed by Béguelin (2011) were also applied, to both male and Table 3.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…These comparisons showed that, when males and females are considered together, individuals from Fuego-Patagonia had a crural index that was most similar to that of the Temperate North American groups (Auerbach and Ruff 2010). Thus, the stature estimation formulae for Temperate groups (Auerbach and Ruff 2010) were applied in this study. Additionally, the formulae developed by Béguelin (2011) were also applied, to both male and Table 3.…”
Section: Resultsmentioning
confidence: 95%
“…The equations are developed based on specific populations that have characteristic body and intralimb proportions. Thus, population specific stature formulae are necessary, and a careful selection of the most appropriate formulae should be based on proportions, such as the crural index, as well as geographic region and genetic origins (Auerbach and Ruff 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method does not rely on calculating stature from a single long bone using regression formulae (the “mathematical method”), but instead produces an estimate based upon the measurement of all of those bones that contribute to height (Raxter et al, 2006, 2007; Maijanen, 2009; Auerbach and Ruff, 2010; Auerbach, 2011; Vercellotti et al, 2014). This provides a more accurate method of calculating living stature, as it is not biased by differences in bodily proportions (Maijanen, 2009; Auerbach and Ruff, 2010; Vercellotti et al, 2014). As studies of stature are increasingly beginning to incorporate vertebral components, it is also now prudent to consider the growth of these skeletal elements.…”
Section: Research Rationalementioning
confidence: 99%